Improved Speech in Noise Perception in the Elderly After 6 Months of Musical Instruction - Worschech, Florian; Marie, Damien; Jünemann, Kristin; Sinke, Christopher; Krüger, Tillmann H. C.; Großbach, Michael; Scholz, Daniel S.; Abdili, Laura; Kliegel, Matthias; James, Clara E.; Altenmüller, Eckart (Frontiers in Neuroscience, 2021)
Understanding speech in background noise poses a challenge in daily communication, which is a particular problem among the elderly. Although musical expertise has often been suggested to be a contributor to speech intelligibility, the associations are mostly correlative. In the present multisite study conducted in Germany and Switzerland, 156 healthy, normal-hearing elderly were randomly assigned to either piano playing or music listening/musical culture groups. The speech reception threshold was assessed using the International Matrix Test before and after a 6 month intervention. Bayesian multilevel modeling revealed an improvement of both groups over time under binaural conditions. Additionally, the speech reception threshold of the piano group decreased during stimuli presentation to the left ear. A right ear improvement only occurred in the German piano group. Furthermore, improvements were predominantly found in women. These findings are discussed in the light of current neuroscientific theories on hemispheric lateralization and biological sex differences. The study indicates a positive transfer from musical training to speech processing, probably supported by the enhancement of auditory processing and improvement of general cognitive functions.